Seasonal trend of Anisakidae infestation in South Mediterranean bluefish. Issue 1 (2nd January 2020) - Cammilleri, Gaetano; Pulvirenti, Andrea; Costa, Antonella; Graci, Stefania; Collura, Rosaria; Buscemi, Maria Drussilla; Sciortino, Sonia; Vitale Badaco, Valeria; Vazzana, Mirella; Brunone, Mariagrazia; Vella, Antonio; Di Bella, Calogero; et al.
Abstract: A total of 1104 fish samples from markets of Sicily were analysed for the detection and species identification of Anisakidae nematodes. The preliminary analysis of the fish samples showed the presence of 2459 larvae. All the fish species revealed different prevalence of infestation, with a maximum of 100% for Lepidopus caudatus and a minimum of 4.5% in Sardina pilchardus. The 80% of the larvae examined by PCR-RFLP analysis belonged to Anisakis pegreffii species. The seasonal infestation trend of Anisakis was evaluated in all the fish sample examined. The results of the seasonal infestation trend showed a marked connection with the ecological aspects of the fish species examined. As far as we know, this work report for the first time important ecological aspects of Lepidopus caudatus specimens of South Mediterranean. This work could be useful to plan a seasonal fishing strategy aimed at reducing the health risks related to Anisakis . Graphical Abstract: